Dramatic story structure a primer for screenwriters - Fink, Edward J. (Edward John) (New York Routledge, 2014)
"A successful screenplay starts with an understanding of the fundamentals of dramatic story structure. In this practical introduction, Edward J. Fink condenses centuries of writing about dramatic theory into ten concise and readable chapters, providing the tools for building an engaging narrative and turning it into an agent-ready script. Fink devotes chapters to the six basic elements of drama from Aristotle's Poetics (plot, character, theme, dialogue, sound, and spectacle), as well as the concepts of unity, metaphor, style, universality, and catharsis. Key terms and discussion questions encourage readers to think through the components of compelling stories and put them into practice, and script formatting guidelines ensure your finished product looks polished and professional. Dramatic Story Structure is an essential resource not only for aspiring screenwriters, but also for experienced practitioners in need of a refresher on the building blocks of storytelling"-- Provided by publisher.
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; Preface; Acknowledgments; 1. Introduction and Sample Script; Drama Defined; Aristotle and Others; Sample Script: La Llorona (The Weeping Woman); 2. Plot; Three-Act Structure; Act 1: Setup to New Direction; Act 2A: Launch of Journey to Midpoint Crisis; Act 2B: All Goes Well to All is Lost; Act 3: Turnaround to Climax and Denouement; Throughout all Three Acts; Experiments with Three-Act Structure; Sample Plot Points; Jule Selbo's 11 Steps (2007); Chris Vogler's 12 Steps (2007), based on Campbell (1949). Eric Edson's 23 Steps (2011)Summary; Reflection and Discussion; 3. Character; Protagonists; Extraordinary Person in Ordinary Situation; Ordinary Person in Extraordinary Situation; Achilles' Heel; Arc; Antagonists; Human v. Human; Human v. Environment; Human v. Self; Supporting Characters; Functionaries; Unmasking; Ethos, Pathos, and Hybris; Experiments with Character; Character Types; Four Humors; Enneagram; Sigmund Freud (1856-1939); Carl Jung (1875-1961); Myers-Briggs; Lajos Egri (1888-1967); Obsession; Summary; Reflection and Discussion; 4. Theme; What Theme Is Not: Plot or Character. What Theme Is: Lesson with Point of ViewTypologies of Theme; Treatment of Theme; Experiments with Theme; Summary; Reflection and Discussion; 5. Dialogue; Show, Don't Tell; Creating Dialogue; Poeticism; Naturalism; Realism; Heightened Realism; Functions of Dialogue; Advance Plot; Reveal Character; Point to Theme; Comprehensibility; Memorable Lines; Dual Meaning; Summary; Reflection and Discussion; 6. Sound; Sound for Screenwriters; Music; Diegetic, Nondiegetic, and Metadiegetic; Parallel and Counterpoint; Sound Effects; Voice; Summary; Reflection and Discussion; 7. Spectacle. Spectacle for ScreenwritersLocations and Sets; Location or Studio; Interior or Exterior; Physical or Virtual; Realistic or Nonrealistic; Lights and Shadow; Costume and Wardrobe; Hair and Makeup; Properties; Actors' Physical Features; Blocking and Camera Shots; Special Effects; Editing; Summary; Reflection and Discussion; 8. Unity, Metaphor, Universality, Catharsis, and Style; Unity; Unity of Action; Unity of Time and Place; Unity of Theme; Metaphor; Universality; Catharsis; Style; Realism and Nonrealism; Tragedy and Comedy; Summary; Reflection and Discussion; 9. Comedy; High and Low Comedy. Schadenfreude and MuditaThree Grand Theories of Comedy: Incongruity, Superiority, and Psychoanalytic (Relief); Incongruity Theory; Superiority Theory; Psychoanalytic or Relief Theory; Comic Structure; Setup and Payoff; Rule of Threes; Running Gag; Double Whammy; Innuendo and Double Entendre; One-Liners and Put-Downs; Summary; Reflection and Discussion; 10. Script Formats; Screenplay Format; Sitcom Format; Two-Column, Split-Page, AV Format; Stage-Play Format; Summary; Reflection and Discussion; References; Index.
Includes bibliographical references (pages 197-204) and index.
Keywords: Motion picture authorship; Television authorship